Knowledge of work-related injury reporting and perceived barriers among janitors. (June 2019) - Green, Deirdre R.; Gerberich, Susan Goodwin; Kim, Hyun; Ryan, Andrew D.; McGovern, Patricia M.; Church, Timothy R.; Schwartz, Adam; Arauz, Rony F.
Abstract: Introduction : The goal of this study was to evaluate and improve janitors' knowledge of workers' rights and responsibilities for assessing and reporting work-related injuries, and to determine the barriers for reporting occupational injuries. Methods : Questionnaires, designed to collect data retrospectively for two, sequential six-month periods, were disseminated to 1200 full-time unionized janitors in the Twin Cities. Immediately following the baseline questionnaire administration, a randomly selected sub-group of janitors (~ 600) received information on workers' rights and responsibilities for reporting injuries; six-months later a questionnaire comparable to the baseline questionnaire was disseminated to the 1200 janitors. Analyses included basic descriptive analyses and identification of potential differences in proportions of job-specific reporting barriers pre-post-intervention. Results : Among the participating janitors (n = 390), approximately half (53%) were initially unsure of what an OSHA 300 Log was; 56% reported not knowing what workers' compensation was. At baseline, in both intervention and non-intervention groups, approximately 25% reported having a perceived barrier to reporting an injury to their employer. Reported barriers included "fear, " "reporting takes too long, " "being unsure of the reporting process, " and an "understanding that injuries are a part of the job." At follow-up, among the intervention group, there was an important reduction (24%–12%) in having a perceived barrier for reporting a work-related injury. Conclusions : A majority of janitors lacked knowledge and awareness of OSHA injury reporting and Workers' Compensation. In order to improve reporting, it is essential to educate employees on OSHA and Workers' Compensation and inform janitors of the injury reporting process through training. Practical applications : Future intervention efforts must focus on the specific barriers for reporting occupational injuries and be tailored specifically to the janitor population. To reduce underreporting of injuries, they must be encouraged to report their occupational injuries. Barriers to reporting these injuries must be eliminated. Highlights: Janitors lack knowledge and awareness of injury reporting in their workplace. There are barriers present that prevent janitors from reporting injuries. Fear of consequences is the most prevalent barrier for reporting an injury. By providing information on injury reporting, barriers were significantly reduced.